Student learning engagement in the online class - Rosi Anjarwati; Lailatus Sa'adah (Universitas Merdeka Malang, 2021)
Learning online in the pandemic era raises a challenge for educators (lecturer). The challenge comes from the effectiveness of online media used and the good atmosphere built in the interactions between lecturers and students. It is due to several factors that may contribute to learning success; one of them is student engagement. This research aimed to explore student engagement in Paragraph Writing online class, involving behavioral, emotional, and cognitive engagement. The participants involved in this study are second-semester students of the English Department at a private college in Jombang. Using a case study, the researchers used observation and questionnaire to obtain the data. Based on the analysis, the results revealed that students tend to be actively engaged in behavioral and cognitive engagement. Furthermore, students’ perception toward their engagement in the dimension of behavior, emotion, and cognition gained positive results. DOI: 10.26905/enjourme.v6i2.6128